Frailty trajectory and its associated factors in older patients undergoing abdominal surgery involving the digestive system: A longitudinal study. - Jing Guo; Wenshuang Wang; Xiaoxue Zhang; Yulin Zheng; Xinran Wang (PLoS ONE)
Frailty is a common multifactorial clinical syndrome in older patients that seriously affects their prognosis. However, most studies to date have ignored the dynamics of frailty. Therefore, we employed a one-month observational longitudinal study to explore frailty trajectories using a latent class growth model. In total, 155 older patients who underwent abdominal surgery involving the digestive system were assessed preoperatively, at discharge, and at the one-month follow-up, and multiple logistic regression analysis was conducted to identify factors influencing frailty trajectories. Four frailty trajectory patterns were identified: no frailty (13.5%), frailty exacerbation (40.0%), frailty improvement (20.0%), and persistent frailty (26.5%). Logistic regression analysis revealed that body mass index, the Charlson comorbidity index score, the type of surgery, the intraoperative drainage tube retention time (drainage time), the first time the patient got out of bed after surgery, the time of the first oral feed after surgery, postoperative complications, mobility, nutritional risk, and anxiety were associated with frailty trajectories. We identified four frailty trajectories in older patients undergoing abdominal surgery involving the digestive system and found that these trajectories were influenced by multiple factors. Focusing on individual specificity is conducive to accurately addressing frailty-associated clinical problems and guiding relevant nursing decisions.